Collaborative Approach for Adolescents with Obsessive-Compulsive Disorder - KOBAYASHI, Naomi; IGARASHI, Toko (Japanese Journal of Behavior Therapy, 2013)
Treatment of obsessive-compulsive disorder in childhood and adolescence requires cognitive behavior therapy (CBT) alone and/or the combination of medication with cognitive behavior therapy. The present case study describes psychotherapy for a high school girl with obsessive-compulsive disorder using a collaborative approach that included the client, her mother, and the therapist. The client had a history of unsuccessful medical and psychiatric single visits due to her resistance to share her symptoms and distress. The psychotherapy employed the treatment program of March & Mulle (2006/2008) ; the client was actively and spontaneously involved in her own treatment. Her symptoms successfully improved after 8 sessions within 4.5 months. Several key issues, such as establishing a trustful therapeutic relationship, as well as a "team" relationship, providing client-focused psycho-education to the client and her mother as her key person, and the clients daily based intervention including home visits are described. Especially, the importance of a collaborative approach for adolescent clients was discussed.